2011
DOI: 10.1007/s10616-011-9392-3
|View full text |Cite
|
Sign up to set email alerts
|

H2O2-induced secretion of tumor necrosis factor-α evokes apoptosis of cardiac myocytes through reactive oxygen species-dependent activation of p38 MAPK

Abstract: P38 mitogen-activated protein kinases (p38 MAPK) and tumor necrosis factor-a (TNF-a) play important roles in oxidative stress-induced apoptosis in cardiac myocytes. However, the regulation and functional role of cross-talk between p38 MAPK and TNF-a pathways have not yet been fully characterized in cardiac myocytes. In this study, we found that inhibition of p38 MAPK with SB-203580 (SB) reduced H 2 O 2 -stimulated secretion of TNF-a, whereas pre-activation of p38 MAPK with sodium arsenite (SA) enhanced H 2 O 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Consistently, our previous study demonstrated that wogonin, another important component of S. baicalensis Georgi, activates ROS to promote TRAIL-induced apoptosis (13). It is also known that the activation of p38 is often mediated by ROS (19)(20)(21)(22). However, the results of the present study revealed that baicalin and TRAIL-induced activation of p38 is independent of ROS.…”
Section: Discussionsupporting
confidence: 90%
“…Consistently, our previous study demonstrated that wogonin, another important component of S. baicalensis Georgi, activates ROS to promote TRAIL-induced apoptosis (13). It is also known that the activation of p38 is often mediated by ROS (19)(20)(21)(22). However, the results of the present study revealed that baicalin and TRAIL-induced activation of p38 is independent of ROS.…”
Section: Discussionsupporting
confidence: 90%
“…cardiomyocyte apoptosis [Chen et al, 2012]. Our results suggest that both b 1 -AA-positive and -negative IgGs might directly activate RAW264.7 cells and promote the secretion of TNF-a, though the effect of b 1 -AA-positive IgGs was more pronounced than that of b 1 -AA-negative IgGs.…”
Section: Discussionmentioning
confidence: 62%
“…Aruldhas et al (2005) supported these results as they stated that direct interaction of reactive chromium intermediates with DNA leading to DNAchromium binding, DNA-protein crosslinks and DNA-DNA crosslinks and they added that interaction of chromium with GSH results in strand breaks and chromium-DNA binding. Chen et al (2012) attributed the DNA damage to the reactive oxygen species ROS that can convert fatty acids to toxic lipid peroxides and could damage every major cellular component.…”
Section: Discussionmentioning
confidence: 99%